Experimental investigation of mechanical and physical properties of glass fiber reinforced concretes produced with different magnetized waters - Heydar Dehghanpour; Yasemin Hatipoğlu; Volkan Ozdal; Muhammed Maraşlı; Doğu Ramazanoğlu; Serkan Subaşı (Journal of Sustainable Construction Materials and Technologies)
Magnetized water may act as a thickener in cementitious mixtures due to its slippery effect. Therefore, it can be beneficial for the mixture to settle easily and to improve its strength. This study investigated the effects of magnetized water passing through pipes with magnetic field intensity (MFI) 8 and 10 on glass fiber reinforced concrete (GFRC). Three different mixtures, the GFRC mixture produced with regular tap water, were obtained, and the properties of the produced GFRC samples, such as 7, 14, and 28 days H-Leeb hardness, density, Ultrasonic pulse velocity (UPV), flexural strength, compressive strength, and fracture mechanics were investigated. In addition, SEM, EDS, FTIR, and TGA analyses were carried out to investigate the change in surface tension in the internal structures of GFRCs produced with magnetized water. Overall, the results were promising. Results showed a proportional H-Leep hardness increase with curing time and density variations. Magnetized water reduced air voids, enhancing sound transmission speeds. Flexural and compressive strength improved with magnetic water. The study suggests significant contributions to energy savings and reduced production costs, highlighting the efficient use of energy resources.